2022
DOI: 10.1039/d1nr07129g
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in polydiacetylene mechanochromism

Abstract: This mini review summarizes recent progress in polydiacetylene (PDA) mechanochromism, with a special focus on the quantitative and nanoscopic data that have emerged in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 82 publications
(93 reference statements)
0
25
0
Order By: Relevance
“…[17][18][19][20][21][22] In particular, the strong chromophoric absorbance of the resulting polydiacetylenes has intrigued many scientists, owing to the reversibility of different phases responsible for blue, purple, and red colours, leading to mechanochromic sensing applications. [23][24][25][26][27][28] Rubner and Sijbesma et al exploited PDAs anchored by bisurea and bisurethanes in hard-soft elastomers to design highly tensile mechanochromic materials. 29,30 Sijbesma et al further demonstrated PDA-based amphiphiles and cross-polymerized hydrogels to furnish interesting biomimetic strain-stiffening materials.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] In particular, the strong chromophoric absorbance of the resulting polydiacetylenes has intrigued many scientists, owing to the reversibility of different phases responsible for blue, purple, and red colours, leading to mechanochromic sensing applications. [23][24][25][26][27][28] Rubner and Sijbesma et al exploited PDAs anchored by bisurea and bisurethanes in hard-soft elastomers to design highly tensile mechanochromic materials. 29,30 Sijbesma et al further demonstrated PDA-based amphiphiles and cross-polymerized hydrogels to furnish interesting biomimetic strain-stiffening materials.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive color-change properties of PDA have been applied to the development of sensing materials. In general, the self-organized structures of DA monomers, such as vesicles and layered structures, provide PDA through the topochemical polymerization with the irradiation of UV light when the distance between the DA moieties is shorter than 0.5 nm in the condensed states . Molecular design, such as changes in the functional groups, chain lengths, and molecular shapes, has been studied in previous works. However, the structural flexibility sufficient to enhance the dynamic properties with molecular motion is not easily achieved by the topochemically polymerizable self-organized structures containing the densely packed molecules.…”
Section: Introductionmentioning
confidence: 99%
“…PDA is a stimuli‐responsive color‐change polymer applicable to sensing. [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] The original blue color is changed to red with the application of external stimuli through shortening of the effective conjugation length. The stimuli responsivity of PDA is controlled by molecular design and intercalation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[ 61 ] Whereas color changes in response to thermal and chemical stresses were extensively studied, responsiveness to mechanical stress was limited in previous works. [ 49 , 50 , 55 , 60 , 62 , 63 , 64 ] In a recent report, the strain applied to the PDA‐contained hydrogel was detected by changes in not the color but the capacitance. [ 65 ] Ultrasonic stress was detected as the shear stress using self‐assembled PDA vesicles.…”
Section: Introductionmentioning
confidence: 99%